USE OF CYSTATIN C DETERMINATION IN CLINICAL DIAGNOSTICS - Mares, Jan; Stejskal, David; Vavrouskova, Jitka; Urbanek, Karel; Herzig, Roman; Hlustik, Petr (Biomedical papers, 2003)
This paper presents a current view of the possible clinical uses of cystatin C determination. Cystatin C is an inhibitor of cysteine proteases, and relatively stable in the systemic circulation it is comparatively easily determined. Although in clinical practice it is known primarily as a relatively reliable and endogenous marker for glomerular filtration, lately cystatin C analysis has been discussed in connection with the diagnostics of a variety of diseases such as early atherosclerosis, Alzheimer's dementia, vascular aneurysms, hyperhomocysteinaemia and other neurodegenerative diseases.
Keywords: Keywords: Cystatin C / Biochemical diagnostics / Alzheimer's dementia / Early atherosclerosis / Vascular aneurysms / Hyperhomocysteinaemia / Neurodegenerative diseases